2020
DOI: 10.1155/2020/3208634
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnobotanical Study of Traditional Knowledge and Uses of Medicinal Wild Plants among the Marakwet Community in Kenya

Abstract: Traditional plant knowledge and uses of medicinal wild plants were investigated among the Marakwet community in Kenya. Data were collected through interviews with seven traditional healers and 157 questionnaires for local community members. Traditional names of the plants by traditional healers and local community members were prepared as a checklist. Loss of traditional medicinal names of plants was ascertained with up to 60% overlapping in their nomenclature. The traditional medicinal plants treated 41 disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
3
25
2
Order By: Relevance
“…2). For a long time, research has shown that old people are the greatest custodians of traditional knowledge of medicinal plant use than the young [18,19,20,21,22,23,24,25,26,27]. The present study however was found to be inconsistent with other studies by showing that the youth are now engaging in utilization and commercialization of medicinal plants.…”
Section: Age and Plant Knowledgecontrasting
confidence: 96%
See 1 more Smart Citation
“…2). For a long time, research has shown that old people are the greatest custodians of traditional knowledge of medicinal plant use than the young [18,19,20,21,22,23,24,25,26,27]. The present study however was found to be inconsistent with other studies by showing that the youth are now engaging in utilization and commercialization of medicinal plants.…”
Section: Age and Plant Knowledgecontrasting
confidence: 96%
“…However, research shows that literacy levels of people determined the mode of treatment [30]; the less educated preferred traditional methods of treatment where as the well educated preferred modern methods of health care. Research over the years has shown low literacy levels among research respondents: [31,32,33,26].…”
Section: Education and Plant Knowledgementioning
confidence: 99%
“…were rare, and were familiar only to the traditional healers and a few local community members. This indicates the issue of knowledge erosion due to modern medicine and other reasons including socio-cultural issues and over exploitation as indicated by Wanjohi et al (2020) in Kenya. In the study area, the local government should ensure adequate income to the community healers and support in cultivation of medicinal plants for effective conservation of biodiversity and traditional knowledge.…”
Section: Threat To Medicinal Plants and Their Conservationmentioning
confidence: 98%
“…Therefore, in this study we determined the IEK of the plant species, use and conservation among the elders and compared that knowledge among the local community members. In Kenya, the Marakwet sub-ethnic group have long history of using plants and therefore large numbers of studies have been conducted in the region (Kipkore et al, 2014;Wanjohi et al, 2020). The elders are custodian of the IEK in their communities while the local residents were supposed to positively identify to help in the preservation of the traditional knowledge.…”
Section: Discussionmentioning
confidence: 99%